POTENSI EKSTRAK METANOL RHIZOM ALANG-ALANG (Imperata cylindrica L.) SEBAGAI BIOHERBISIDA PENGHAMBAT PERTUMBUHAN GULMA SEMBUNG RAMBAT (Mikania micrantha H.B.K) - Egidia Egidia; Mukarlina Mukarlina; Riza Linda (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Imperata cylindrica is a narrow-leaved weed that contains phenol compounds in the form of flavonoids and tannins that can inhibit the growth of other plants, so it has the potential as a bioherbicide. The purpose of this study was to determine the effect of methanol extract of rhizom I. cylindrica on the germination and growth of Mikania micrantha weed and to determine the concentration of methanol extract of rhizom I. cylindrica that well inhibits the germination and growth of M. micrantha weed. This research started from March to December 2023 and was carried out at the Forest Products Chemistry Laboratory Faculty of Forestry, Laboratory and Cassa House Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. The method used in this research is Completely Randomized Design (CRD) with 5 concentration treatments of 0 g/ml (control); 0.1 g/ml; 0.2 g/ml; 0.3 g/ml and 0.4 g/ml, each treatment consists of 5 replicates. The results showed that methanol extract of rhizom I. cylindrica gave a significant effect on the germination and growth of M. micrantha weed. The methanol extract of rhizom I. cylindrica that best inhibits the germination of M. micrantha weed is a concentration of 0.2 g/ml and best inhibits the growth of M. micrantha weed is a concentration of 0.4 g/ml. Methanol extract of rhizom I. cylindrica has the potential as a bioherbicide to inhibit the growth of M. micrantha weed.